Socialization of the Importance of Saving from an Early Age to Elementary School Students in Bongas Village, Indramayu Regency - Anisa Dewi (Konsultan Jurnal Ilmiah Indonesia, 2025)
Saving is the activity of setting aside some of the money or income you have for savings with the aim of managing that money. The benefits of saving can be obtained when we carry out this saving activity regularly and diligently. This aims to lead a frugal lifestyle and is also a characteristic development of not wasting money which should be implemented from an early age. In this community service activity, there was a socialization about